Phylogenetic relationships of the wolf spider genus Orinocosa Chamberlin, 1916 : (Araneae, Lycosidae) - Munguía, Williams Paredes (2013)
There are few studies that have tried to resolve the phylogenetic relationships of Lycosidae until now. The current studies on phylogeny used genes to discover and explain the intergeneric relationships of the family. In this work, all the Orinocosa species distributed worldwide and poor little known genus of Lycosidae was studied. Orinocosa species were analyzed to discover their internal and external phylogenetic relationships. A total of 27 taxa were placed as internal group and 23 taxa belonging to 17 genera, which formed the outgroup were analyzed. A total of 114 characters were obtained in this analysis, most binary and discrete, between sexual and non-sexual. The out-group was represented by at least two species of four subfamilies considered in this study, making a total of 52 taxa analyzed. Agalenocosa was one of the genera included in a data matrix phylogenetic here for the first time. The construction of the data matrix was made in the program Mesquite and the resulting trees, as well as the consensus tree have been edited in Winclada. Data were analyzed by heuristic search and then the new technologies included in the software ASADO that uses the algorithms of TNT and NONA. This analysis resulted in a total of five most parsimonious trees, each fully resolved, with the following values for consensus: L = 884, C = 18 and R = 40. The value of Bremmer support to Orinocosa was two; for the rest of the branches varied between one and three. Orinocosa sensu stricto emerged as a polyphyletic group. The new proposal of Orinocosa was supported by two non-homoplasious characters: absence of stridulatory organ and ventral keel of Median Apophysis straight. From all species belonging and revised to the group of Orinocosa, 60% of them do not belong to the genus. In conclusion, the merely female of Orinocosa aymara correspond to the original description, the other species did not fit with the concept of Orinocosa and will be transferred based on the diagnostic generic characters in a future proposal. Of the 21 morphospecies of Orinocosa, only 16 were grouped within the genus. The remaining morphospecies were allocated outside the genre, probably because the only female in each terminal. Trochosa proved to be the sister group of Orinocosa. It is suggested in the future to include more Trochosa species to get wider and complete resolution.